Pengembangan Objek Wisata Hutan Mangrove Di Kelurahan Lakologou Kota Baubau: Pengembangan Objek Wisata Hutan Mangrove Di Kelurahan Lakologou Kota Baubau - La Ode, Helmawan; Amin, Hartini (LeRIn - Universitas Dayanu Ikhsanuddin - Prodi. Sosiologi, 2025)
This study examines strategies for developing mangrove forest tourism in Lakologou Village, Baubau City, with an emphasis on integrating environmental sustainability, strengthening community social capacity, and optimizing the use of local potential. Tourism visitation data indicate that the domestic market remains dominant, while the prospect for attracting international tourists is still largely untapped. Although the Lakologou mangrove tourism area holds considerable ecological, educational, and economic value, it has yet to become a primary focus within the regional tourism policy framework. Employing a descriptive qualitative approach, the research utilized observation, interviews, and documentation, with data analyzed through processes of reduction, presentation, and conclusion drawing. Findings reveal that the success of site management is shaped by internal factors, such as active community participation, ecological awareness, and local wisdom, as well as external factors, including governmental policy support, infrastructure availability, and human resource capacity.